Telaah Manusia Kontemporer Dalam Menuju Kesempurnaan - Nova Mariyanti; Yogi Fernando; Wedra Aprison (Jurnal Pendidikan Indonesia (JOUPI), 2023)
Humans themselves are special and special creatures. With this specialty, there are still many mysteries that cannot be revealed within humans, including regarding perfection. Let alone regarding perfection, even regarding human understanding itself, the experts out there have not reached a consensus in agreeing on human understanding. However, in essence, humans are servants of Allah SWT who must always worship Him, so that they can hopefully reach the point of perfection. This research itself is qualitative research with a literature review approach. From the research that the author has carried out, it is found that contemporary humans today will find it difficult to achieve perfection. Because from the study that the author has tried to explain, this perfection can only be done by always worshiping Allah, sharpening your mind and mind as well as knowledge and also maintaining hablum minannas. This is very different from contemporary humans today who are far from God and even indulge in lust and laziness.